RELASI KESALINGAN DALAM RUMAH TANGGA: KAJIAN ATAS POLA HUBUNGAN SUAMI-ISTRI PERSPEKTIF MUBADALAH - Tiara Cintia Maneza; Jumni Nelli; Afrizal Ahmad (CV. Denasya Smart Publisher, 2026)
This study analyzes the patterns of husband-wife relationships based on the mubadalah perspective, which emphasizes reciprocity, fairness, and cooperation in the household. The study was conducted in Sidomulyo Timur Village, Marpoyan Damai District, Pekanbaru City, using a qualitative approach and in-depth interviews with married couples as the main informants. The results of the study identified four developing relationship patterns: (1) Owner–Property, (2) Head–Complement, (3) Senior–Junior, and (4) Equal Partner. Among these four patterns, only the Equal Partner pattern fully reflects the values of mubadalah, while the other patterns show variations in the level of equality and involvement of the couple. This study concludes that an ideal husband-wife relationship should be built on the principles of mubadalah and taradhin (mutual consent) in order to achieve a harmonious, fair, and equal household.